Flexible Meander-Line Antenna Array for Wearable Electromagnetic Head Imaging - Alqadami, Abdulrahman. S. M.; Stancombe, Anthony E.; Bialkowski, Konstanty S.; Abbosh, Amin (IEEE transactions on antennas and propagation, 2021)
Portable lightweight electromagnetic (EM) head imaging systems for brain stroke detection are of great interest due to the need for fast and low-cost diagnosis tools. This communication presents a wideband and compact flexible meander-line antenna array for a wearable EM head imaging system. The antenna is designed and optimized on a 4 mm thick low-cost, flexible room-temperature-vulcanizing (RTV) silicone substrate in close vicinity to a multitissue head model. The antenna comprises two sections of meander-lines, a full ground plane, and a 50~Ω coaxial connector. The measured reflection coefficient \vert \text{S}_{11}\vert on a human head shows that the proposed antenna operates effectively across the frequency band of 0.45-3.6 GHz, attaining fractional bandwidth (FBW) of 155%. The antenna achieves unidirectional radiations with greater than 9 dB of front-to-rear ratio in the near-field region, and safe-level maximum specific-absorption rate (SAR) below 0.2 W/kg using an input power of 10 dBm. A 16 element antenna array was assembled and experimentally utilized in an EM head imaging system. The reconstructed images of abnormality-emulating targets using a confocal imaging algorithm demonstrate the feasibility of utilizing such flexible and lightweight antennas for wearable EM head imaging systems.